ANÁLISE SOCIOAMBIENTAL E DOENÇAS DE VEICULAÇÃO HÍDRICA NOS MUNICÍPIOS DE MATINHA E MONÇÃO – MARANHÃO - SOARES, Jacenilde Cristina Braga (2019)
The water contamination represents a risk to society's health, especially the most vulnerable population, SINCE these are those who live in precarious conditions due to the limitation of basic sanitation services, compromising the well-being of the population. In Maranhão, it is estimated that 45.3% of the population does not have access to drinking water. In this context, the research aimed to analyze the influence of socio-environmental and health conditions and the occurrence of waterborne diseases in the municipalities of Matinha and Monção, located in Baixada Maranhense, in the years 2015 and 2016. The research is descriptive and exploratory, using the inductive method with a qualitative and quantitative approach, and the choice of the two municipalities was related to the points of collection of the microbiological analyzes performed by Bastos (2016), in the urban area of Matinha and Monção. Were applied 30 questionnaires in each municipality in September 2018, taking into account the areas in which the highest values of microorganisms that were detected in samples collected and analyzed by Bastos (2016). The collected data were tabulated in the Microsoft Excel 2018 program. The result of the tabulation made it possible to create the graphs for a better presentation of the results. In addition, visits were made to apply the questionnaires. To make the maps, the geoprocessing software Qgis 3.8.3 was used. The municipalities of Matinha and Monção have a privileged territory in terms of water potential, however, this situation is worrying, since both have an unsatisfactory basic sanitation system. The use of septic tanks was observed in more than 80% of households in both municipalities. The water is captured through wells, serving the entire urban area, however, 40% in Monção and 23% in Matinha use alternative sources such as shallow wells and springs, where over half of the respondents make no treatment in water consumed. Municipalities data showed a high number of cases of diarrhea and gastroenteritis, with a total of 173 cases in Matinha and 124 in Monção, totaling 297 cases in 2015. In 2016 there was a prevalence in the number of cases totaling 427 cases. The period of high rainfall was the one that registered the most cases. with regard to the treatment of diarrhea, 80% of respondents claimed to do this procedure at home. Remember that microbiological analyzes these municipalities showed high content of microorganisms that cause waterborne diseases. It is understood that environmental factors such as soil characteristics, slope, rainfall and river system, associated with health conditions affect water quality and compromise the quality of life and health of residents. Thus, the municipalities studied need a system for monitoring the quality of water destined for public supply. It is suggested that integrated actions be developed for sanitation, education and health care policies that take into account inequalities and contribute to improving the health conditions of the population and health indicators in the municipalities.